Model Prototype pada Pengembangan Sistem Informasi Admininistrasi Pendisiplinan Siswa (Studi Kasus: SMA Negeri 8 Kota Bengkulu) - Niska Ramadani; Amdhi Yul, Fadlul; Prasetyo, Cahyo (Universitas Putra Indonesia YPTK Padang, 2023)
Development of Information System for Student Disciplinary Administration (SIPS) is a system used to manage student disciplinary data, so that it can facilitate officers in recording students who commit violations and follow up on student violations. The student disciplinary information system is built using the PHP Programming Language with CodeIgniter and MySql database, the problem analysis method used is the PIECES method, in developing the system using the Prototype model. From the results of the study it is known that the data collection of student violations at SMA Negeri 8 Bengkulu City which is currently being carried out by recording student data in the book, and for follow-up violations only written on memo paper, and there is no reporting for student discipline, therefore it is necessary to build a Student Disciplinary Information System (SIPS) at SMAN 8 Bengkulu City to provide information about student violation data, which can be stored in the database.